2013
DOI: 10.1016/j.otsr.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of first metatarsophalangeal joint lateral release in hallux valgus surgery

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This has been proven experimentally [11,12,14] and clinically [7,20,27]. Preferably this ligament should be transected under direct vision after incision of the lateral Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This has been proven experimentally [11,12,14] and clinically [7,20,27]. Preferably this ligament should be transected under direct vision after incision of the lateral Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The lateral metatarsosesamoid suspensory ligament is the key to a successful lateral release [8,14,20]: Corrections of MTP and IM angles to physiological values are achieved only when the ligamentous connection between the metatarsal head and the lateral sesamoid is transected completely. At the same time, reduction of sesamoid luxation is only possible when the lateral metatarsosesamoid suspensory ligament is transected.…”
Section: The Anatomymentioning
confidence: 99%
“…It has recently been suggested that preoperative incongruity of the first metatarsophalangeal joint has the greatest effect on the rate of recurrence. 41,42 Soft-tissue factors, such as the adequacy of the lateral release, may also contribute to the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed if the transverse metatarsal ligament were to be divided this would lead to an increase mobility in all planes [8]. In clinical practice Augoyard et al demonstrated through progressive division of the metatarosesamoid suspensory ligament and phalangeal insertional band that lateral soft tissue release was achieved in most cases whilst adductor release from the lateral sesamoid had limited value [24].…”
Section: Discussionmentioning
confidence: 99%